Research in labor economics - Polachek, S. W.; Tatsiramos, Konstantinos (Research in labor economics, 2012)
This volume contains eight research articles relevant to researchers and policy makers. Each chapter deals with an aspect of human welfare and is authored by an expert in the field. One deals with how technological change affects the distribution of earnings, two deal with how workers advance through corporate hierarchy, four deal with how incentives motivate workers, and the final chapter deals with how one immigrant group is far more successful than even the native population.